NEW GENERATION ENTERPRISE GEOGRAPHIC INFORMATION SYSTEMS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
This paper addresses common problems like poor reusability, closed vendor proprietary framework, limited customizability which are associated with use of traditional Geographic Information Systems (GIS) and proposes architecture of new generation GIS. The architecture described in this paper is based on Service Oriented Architecture and open standards. It consists of Geographic Information Service Provider, Geographic Information Service Consumer and Geographic Information Mediation Infrastructure. The new generation GIS allows achieving high level of reusability both on GIS logic and orchestration layer. Its broad customizability capabilities make it suitable for wide user audience.